2019
DOI: 10.1097/j.pain.0000000000001697
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic therapeutic response in bortezomib-induced neuropathic pain reveals altered pain physiology in female rodents

Abstract: Chemotherapy-induced neuropathic pain (CINP) in both sexes compromises many current chemotherapeutics and lacks a FDA-approved therapy. We recently identified the sphingosine-1phosphate receptor subtype 1 (S1PR1) and A 3 adenosine receptor subtype (A 3 AR) as novel targets for therapeutic intervention. Our work in male rodents using paclitaxel, oxaliplatin and bortezomib showed robust inhibition of CINP with either S1PR1 antagonists or A 3 AR agonists. The S1PR1 functional antagonist FTY720 (Gilenya®) is FDA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Moreover, mice with specific deletion of S1PR1 on astrocytes do not develop CINP, underscoring the importance of an astrocyte-based S1PR1 signaling pathway in these conditions [99]. Importantly, sex differences in drug responses to bortezomib-induced neuropathic pain (BINP) have been reported [111]. In particular, S1PR1 antagonists, which alleviate paclitaxel and oxaliplatin CINP in both sexes, failed to prevent and reverse BINP in female rodents [111].…”
Section: Exploiting S1p Signaling Towards Managing Chronic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, mice with specific deletion of S1PR1 on astrocytes do not develop CINP, underscoring the importance of an astrocyte-based S1PR1 signaling pathway in these conditions [99]. Importantly, sex differences in drug responses to bortezomib-induced neuropathic pain (BINP) have been reported [111]. In particular, S1PR1 antagonists, which alleviate paclitaxel and oxaliplatin CINP in both sexes, failed to prevent and reverse BINP in female rodents [111].…”
Section: Exploiting S1p Signaling Towards Managing Chronic Painmentioning
confidence: 99%
“…Importantly, sex differences in drug responses to bortezomib-induced neuropathic pain (BINP) have been reported [111]. In particular, S1PR1 antagonists, which alleviate paclitaxel and oxaliplatin CINP in both sexes, failed to prevent and reverse BINP in female rodents [111]. These data are particularly relevant and have to be considered in the clinical translation of these compounds, since S1PR1-based therapies could be ineffective in the treatment of CINP in women who receive bortezomib chemotherapy.…”
Section: Exploiting S1p Signaling Towards Managing Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that sphingosine-1-phosphate receptor subtype 1 (S1PR1) antagonists and A 3 adenosine receptor subtype (A 3 AR) agonists suppressed the oxaliplatin- and paclitaxel-induced neuropathy in male and female rats, but S1PR1 antagonists and A 3 AR agonists only inhibited the bortezomib-induced neuropathy in male rats. [ 64 ]. It has also indicated that resolvin D5 inhibited the paclitaxel-induced mechanical allodynia in male mice, but did not affect female mice [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of sphingosine-kinase blocks the neuroprotective effect of NGF, suggesting that S1P is involved in NGF-mediated survival in neuron cultures, and the excitatory effect of NGF introducing nociceptor sensitization and hyperalgesia also dependents on S1P production [146,227]. To some extent, the precise contribution of S1P1 and S1P2 as potential analgesic drug targets for paclitaxel, oxaliplatin, and bortezomib induced neuropathic pain are conversely discussed and even sex differences in responses to S1P receptor antagonists are reported [228]. Altogether, drugs targeting the ceramide to S1P pathway, specifically S1P2 agonists, are more and more emerging as an adjuvant therapeutic strategy for enhancing chemotherapy effectiveness and reduction of painful neuropathies and thus may represent a promising therapeutic approach for the management of chemotherapy-induced neuropathy.…”
Section: Painful Chemotherapy-induced Peripheral Neuropathy (Cipn)mentioning
confidence: 99%